2007
DOI: 10.1021/bi700429z
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Mobility and Microdomain Association of the Dopamine Transporter Studied with Fluorescence Correlation Spectroscopy and Fluorescence Recovery after Photobleaching

Abstract: To investigate microdomain association of the dopamine transporter (DAT), we employed FCS (fluorescence correlation spectroscopy) and FRAP (fluorescence recovery after photobleaching). In non-neuronal cells (HEK293), FCS measurements revealed for the YFP-DAT (DAT tagged with yellow fluorescent protein) a diffusion coefficient (D) of approximately 3.6 x 10(-9) cm2/s, consistent with a relatively freely diffusible protein. In neuronally derived cells (N2a), we were unable to perform FCS measurements on plasma me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
160
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(174 citation statements)
references
References 50 publications
12
160
2
Order By: Relevance
“…Previous studies reported that DAT partitions between lipid raft and nonraft plasma membrane microdomains (Adkins et al, 2007;Foster et al, 2008;Cremona et al, 2011;Navaroli et al, 2011), and that flotillin-1 retains DAT in lipid rafts (Cremona et al, 2011;Sorkina et al, 2013) and is required for PKC-stimulated DAT endocytosis (Cremona et al, 2011) in HEK cells. Thus, we asked whether the endocytic-willing DAT surface pool preferentially arises from either raft or nonraft loci in SK-N-MC cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that DAT partitions between lipid raft and nonraft plasma membrane microdomains (Adkins et al, 2007;Foster et al, 2008;Cremona et al, 2011;Navaroli et al, 2011), and that flotillin-1 retains DAT in lipid rafts (Cremona et al, 2011;Sorkina et al, 2013) and is required for PKC-stimulated DAT endocytosis (Cremona et al, 2011) in HEK cells. Thus, we asked whether the endocytic-willing DAT surface pool preferentially arises from either raft or nonraft loci in SK-N-MC cells.…”
Section: Resultsmentioning
confidence: 99%
“…To date, DAT trafficking studies have been performed primarily in non-neuronal cell lines or cultured midbrain neurons derived from P0-P2 rodents, which may not faithfully recapitulate endocytic mechanisms inherent in adult dopaminergic neurons. Studies comparing DAT surface dynamics in HEK versus Neuro2A cells similarly found striking differences in DAT lateral mobility between the two cell types (Adkins et al, 2007). Indeed, our current results comparing PC12 cells, SK-N-MC cells and striatal slices clearly demonstrate that DAT's dynamin dependence is highly sensitive to cellular context (Figs.1-3).Interestingly,SK-N-MCcellsidentically recapitulated striatal slice results, suggesting that SK-N-MC neuroblastoma is a reliable culture model for constitutive and PKC-stimulated DAT internalization studies.…”
Section: Discussionmentioning
confidence: 99%
“…DAT activity has been shown to be regulated by the stabilization or distribution of the transporter in the cholesterol-rich membrane microdomains (40,54,55). Because ␣-synuclein has been shown to recruit the GM1 gangliosides to the plasma membrane (57), the measured increase in co-localization of DAT with the CTx-B-labeled GM1 gangliosides in Fig.…”
Section: Discussionmentioning
confidence: 96%
“…␣-Synuclein Alters Membrane Microdomain Distribution of DAT-DAT is distributed in the cholesterol-rich and cholesterol-poor membrane microdomains termed membrane rafts (40,54,55). Previous studies support the idea that membrane microdomain distribution of DAT influences its conformational state and its function (54,55).…”
Section: Dopamine Transporter and ␣-Synucleinmentioning
confidence: 90%
See 1 more Smart Citation